Illegal Labour Activity: Trends in State Risk Minimization - L. N. Orlova; O. V. Lifanovskaya (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
Illegal labour activity is a multi-sided notion, which shows a whole set of processes dealing with arising, realizing and terminating labour relations between worker and employer, in case infringement of law and formal standards takes place. The goal of the research is to work out trends of lowering risks of illegal labour activity in national and sectoral aspects. The authors formed the methodological basis of the research by materials of investigations in the field of economic security and shadow economy, illegal and informal labour activity and risk management. Statistic and analytical materials of international and national statistic services were used as information foundation of the research. In the research the authors used general-scientific and specific economic methods that allow us to study the problem of illegal labour activity in a complex way, for instance, content-analysis, statistic analysis, revealing cause and effect links. Serious attention was paid to finding reasons and consequences of illegal labour activity and key branches of economy, where processes of illegal labour activity are the most obvious. Practical importance of the research is connected with using tools of risk management in state regulation and identifying measures of counteraction and barring cases of illegal labour activity. According to the authors state regulation in the field of illegal labour activity shall be based on monitoring and analysis of social and economic situation, forecasting trends and specification of plans of social and economic development.